The Level of Hormone Testosterone, Sperm quality, Testes and Uropygium size of Male Quails (Coturnix coturnix japonica) Based On Differences Age - Abyadul Fitriyah; Supriyono Supriyono; Isyaturriyadhah Isyaturriyadhah (Universitas Muara Bungo, 2017)
The research was conducted to know The level of hormone testosterone, sperm quality, testes and uropygium size ofmale quails (coturnix coturnix japonica) based on differences in age. The research used each forty 4-w old malequails, 6-w old male quails, 8-w old male quails and 10-w old male quails. The quails were given feed with the samecomposition of diets are crude protein (20.51%), fat (4.46%), crude fiber (4.38%), calcium (1.54%), phosphor (0.77%)and energy metabolism (2602.01 Kcal/kg). The quality of the quail feed material, it is analyzed the proximate of theration (corn, rice bran, soya bean meal, meat bone meal, CaCO3, DL-metionin, L-lysine, NaCl and premix). Variablesobserved: hormone testosterone level, body weight, sperm quality (motility, morphology, viability and concentration),testes size (weight, length, circulation and volume), and uropygium size. The sperm quality data (sperm motility, spermmorphology, sperm viability and sperm concentration) were analyzed by Duncan Multiple Range Test (DMRT). Theother data were analyzed descriptively. The output of this research showed that: The average of hormone testosteronelevel of forty 6, 8 and 10-w old quails are (1.68 ng/ml), (3.08 ng/ml) and (4.92 ng/ml), and the lowest hormonetestosterone level showed at 4-w old quails. The average body weight of forty 4-w old quails (55.8 g), forty 6-w oldquails (103.0 g), forty 8-w old quails (135.0 g) and forty 10-w old quails (152.0 g). The highest sperm quality showed atforty 10-w old quails with the average of sperm motility (78.30 %), sperm morphology (76.70 % of sperm normal),sperm viability (73.19 % of sperm life) and sperm concentration (250 x 109/ml). Sperm quality of forty 4, 6 and 8-w oldquails not significance difference. The highest testes size and uropygium size showed at forty 10-w old quails with theaverage of testes weight (2.64 g); uropygium (2.90 g), testes length (2.0 cm), testes circle (4.7 cm), testes volume (2.0ml) and uropygium diameter (5.70 cm). The lowest testes and uropygium size showed at forty 4-w old quails. Testesand uropygium size of forty 6 and 8-w old quails not significance difference. The conclusion of this research: the levelof hormone testosterone, sperm quality, testes and uropygium size of forty 6 to 10-w old male quails have higher qualityrather than forty 4-w old male quails and the highest quality showed at forty 10-w old male quails.Key words: Hormone testosterone, sperm quality, testes, uropygium, male quails